Roberto Caracciolo da Lecce (1425-1495): life, works, and fame of a Renaissance preacher - Mariani, Giacomo (The medieval Franciscans, 2022)
Franciscan historiography concerning a controversial friar -- The influence of defaming comments and the waning of a style of preaching -- Youth and family (1425-c.1446) -- First successful preaching in Umbria (c.1446-1448) -- Itinerant preaching in central and southern Italy (1448-1450) -- Preaching in Padua (1450-1451) -- Brescia, Milan, and Forli̇ (1451) -- Roberto's break from the observant family (1452-1453) -- Renewed attacks against the observant reform (1453-1455) -- Preaching the crusade in Rome (1455-1457) -- Preaching in Milan (1457-1458) -- Florence and Rome (1459-1461) -- Preaching the crusade in Northern Italy (1463) -- Rome, Bologna, Ferrara, Naples and Genoa (1464-1467) -- The Devil's activity in the world (1467-1470) -- Preacher in Naples and ecclesiastical career in Rome (1470-1480) -- From the siege of Otranto to the last years in Lecce (1480-1495) -- Preaching between action and intellectual debate -- Preaching, writing, and printing sermons in fifteenth-century Italy -- The editorial history of Roberto's sermon collections -- Outlines of the manuscript diffusion of Roberto's sermons -- The readers of Roberto's sermon collections -- The fame of the celebrated preacher.